Strong and ductile refractory high-entropy alloys with super formability - Zhang, C; Wang, H; Wang, X; Yu, Q; Zhu, C; Xu, M; Zhao, S; Kou, R; Wang, X; MacDonald, BE; Reed, RC; Vecchio, KS; et al. (Elsevier, 2022)
Refractory high-entropy alloys (RHEAs) are considered promising candidate materials for high-temperature structural applications that currently use superalloys. However, for most of the reported RHEAs, their poor ductility and negligible cold-workability at room temperature have hindered their use. Here, we report a new class of non-equiatomic NbTaTi-based RHEAs that can be cold-rolled to a reduction of over 90% from the as-cast state without surface treatment and/or intermediate annealing. This excellent cold-workability is facilitated by activation of a high-density of dislocations and deformation twins as well as by high diffusivity paths, such that these RHEAs can be rendered homogeneous at lower annealing temperatures for much shorter time durations. In addition, we report that the RHEAs retain their high strength at elevated temperatures and exhibit considerable ductility at cryogenic conditions, evading the traditional strength–ductility trade-off. This class of super-formable RHEAs provides a novel design pathway to fabricate high-temperature structural materials via an energy- and time-saving method.